Assistance in Compost and POC Production at SD Muhammadiyah 4, Samarinda, East Kalimantan - Aulia, Najwa; Pramaningsih, Vita; Agustina, Fitriyati; Saputra, Harun; Atoillah, Nizar; Kurniawan, Deny (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2025)
The waste problem is a global challenge that is faced daily, including in Indonesia. Organic waste that is not appropriately managed can hurt the environment. One effective solution is to process organic waste into compost and liquid organic fertilizer (POC). This activity aims to practice organic waste processing methods through training for students and teachers at SD Muhammadiyah 4, Samarinda, East Kalimantan. The methods used are Project-Based Learning (PBL), which includes socialization to increase environmental awareness and training in practical composting and POC. The parameters measured include temperature and pH to monitor the composting and fermentation processes. The results of the activity showed that the participants were able to process organic waste into fertilizer well. Compost has an acidic pH (4-6) because lime is not added during the composting process. POC has a pH of 4, indicating effective fermentation activity. The temperature at POC ranged from 26°C to 28°C, with the highest temperature on day 12 indicating maximum degradation. This service activity increases participants' understanding and skills regarding organic waste processing. This activity also encourages schools to actively manage waste independently, creating a cleaner and more sustainable environment.